Herpetic whitlow in an infant - Yanfei LI; Hongxia YAN; Baopeng QI; Jingxue GUO; Qiri MU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
We report a case of herpetic whitlow in an infant. A 1-year-old baby presented with swelling and erythema of the middle finger in the left hand for more than 1 week. Dermatological examination: there was little transparent blister and perinail erythema of the distal middle finger of left hand. It was positive for herpes simplex virus type 1 (HSV-1) by polymerase chain reaction (PCR) dection. A diagnosis of herpetic whitlow was made for this patient. No special treatment was given. The lesions were recovered spontaneously after 10 days. There was no recurrence after 3 months follow-up.